Public health information on COVID-19 for international travellers: lessons learned from a mixed-method evaluation. (April 2021) - Zhang, T.; Robin, C.; Cai, S.; Sawyer, C.; Rice, W.; Smith, L.E.; Amlôt, R.; Rubin, G.J.; Reynolds, R.; Yardley, L.; Hickman, M.; Oliver, I.; et al.
Abstract: Objectives: In the containment phase of the response to the COVID-19 outbreak, Public Health England (PHE) delivered advice to travellers arriving at major UK ports. We aimed to rapidly evaluate the impact and effectiveness of these communication materials for passengers in the early stages of the pandemic. Study design: The study design used is the mixed-methods evaluation. Methods: A questionnaire survey and follow-up interviews with passengers arriving at London Heathrow Airport on scheduled flights from China and Singapore. The survey assessed passengers' knowledge of symptoms, actions to take, and attitudes towards PHE COVID-19 public health information; interviews explored their views of official public health information and self-isolation. Results: One hundred and twenty-one passengers participated in the survey and 15 in follow-up interviews. Eighty three percentage of surveyed passengers correctly identified all three COVID-19 associated symptoms listed in PHE information at that time. Most could identify the recommended actions and found the advice understandable and trustworthy. Interviews revealed that passengers shared concerns about the lack of wider official action, and that passengers' knowledge had been acquired elsewhere as much from PHE. Respondents also noted their own agency in choosing to self-isolate, partially as a self-protective measure. Conclusion: PHE COVID-19 public health information was perceived as clear and acceptable, but we found that passengers acquired knowledge from various sources and they saw the provision of information alone on arrival as an insufficient official response. Our study provides fresh insights into the importance of taking greater account of diverse information sources and of the need for public assurance in creating public health information materials to address global health threats.